On \((1, 2)^\)-\(g_α\)-closed Sets
We introduce a new class of sets namely \((1, 2)^\)-\(g_α\)-closed sets, \((1, 2)^\)-\(Λ_G \)-set, \((1, 2)^\)-\(λ_G \)-set and \((1, 2)^\)-\(g_α\)-Locally closed sets are study in bitopological spaces. We prove that this classes lies between \((1, 2)^\)-\(α\)-closed sets and \((1, 2)^\)-\(α g\)-closed sets. Furthermore, we discuss some essential properties of \((1, 2)^\)-\(g_α\)-closed sets in present of this paper. , number=1, journal=Communications in Mathematics and Applications, author=Ponmalar, A. and Asokan, R. and Nethaji, O., year=2021, month=Dec., pages=307–314